Kedudukan Sertifikat Sebagai Alat Bukti Yang Kuat Menurut Hukum Positif dan Hukum Islam - Shely Melynia; Ema Fathimah; Gibtiah Gibtiah (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Abstract: This article aims to understand the position of certificates as legal evidence according to Law Number 5 of 1960 article 19 paragraph (2) letter c and Islamic law. The method used by the author in this article is a normative legal research method. The approach method used is a comparative approach. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that the certificate in the view of Islamic Law is proof and a strong certainty for the certificate holder itself. Meanwhile, according to Law Number 5 of 1960 Article 19 paragraph (2) letter c, certificates are very strong for proof before a court as long as there is no evidence to prove that the certificate is not true or false, both from physical data and juridical data. The similarity of the two laws is that the certificate must be issued from the local land office and known or signed by the official who made the deed or land certificate. And also in the certificate must include physical data and juridical data to obtain certainty and be recognized by the court as long as there is no evidence to the contrary.